2007
DOI: 10.1128/aem.01944-06
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of a Phylogenetically Complex Microbial Consortium in the Viviparous SpongeIrcinia felix

Abstract: Many marine demosponges contain large amounts of phylogenetically complex yet highly sponge-specific microbial consortia within the mesohyl matrix, but little is known about how these microorganisms are acquired by their hosts. Settlement experiments were performed with the viviparous Caribbean demosponge Ircinia felix to investigate the role of larvae in the vertical transmission of the sponge-associated microbial community. Inspections by electron microscopy revealed large amounts of morphologically diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 54 publications
8
105
0
Order By: Relevance
“…Such a co-speciation pattern, where closely related sponges contain more similar microbial communities compared with distantly related sponges, would be expected if sponge symbionts were strictly transmitted via reproductive stages to the next generation. Vertical transmission of single lineages and of complex microbial communities has been shown for several sponges including some of the species investigated in this study (Usher et al, 2001;Oren et al, 2005;Enticknap et al, 2006;Schmitt et al, 2007;Sharp et al, 2007). However, it was previously proposed that vertical transmission is not the only mechanism of symbiont acquisition and that sponge symbionts may additionally be acquired from the seawater (Taylor et al, 2007;Schmitt et al, 2008;Webster et al, 2010).…”
Section: Resultsmentioning
confidence: 74%
“…Such a co-speciation pattern, where closely related sponges contain more similar microbial communities compared with distantly related sponges, would be expected if sponge symbionts were strictly transmitted via reproductive stages to the next generation. Vertical transmission of single lineages and of complex microbial communities has been shown for several sponges including some of the species investigated in this study (Usher et al, 2001;Oren et al, 2005;Enticknap et al, 2006;Schmitt et al, 2007;Sharp et al, 2007). However, it was previously proposed that vertical transmission is not the only mechanism of symbiont acquisition and that sponge symbionts may additionally be acquired from the seawater (Taylor et al, 2007;Schmitt et al, 2008;Webster et al, 2010).…”
Section: Resultsmentioning
confidence: 74%
“…A typical HMA sponge contains 10 8 to 10 10 microorganisms/g sponge tissue, which can make up to 20%-35% of the sponge biomass (Reiswig, 1981;Webster et al, 2001;Hentschel et al, 2012); in contrast, only 10 5 to 10 6 bacteria/g sponge tissue are found in LMA sponges, which is roughly equivalent to the microbial abundances in seawater (Hentschel et al, 2006). This pattern extends to reproductive propagules in that the larvae of HMA sponges contain dense bacterial assemblages at the larval center, while the interior of LMA sponge larvae is largely free of microbes (Ereskovsky and Tokina, 2004;Maldonado, 2007;Schmitt et al, 2007;Gloeckner et al, 2013a, b). Vertical microbial transmission from the parent to the larva, a hallmark of symbiotic hostmicrobe associations (Bright and Bulgheresi, 2010), is now considered an important and presumably evolutionarily ancient component of HMA sponge symbioses.…”
Section: Introductionmentioning
confidence: 85%
“…Similarly diverse microbial communities were found in larvae of the sponges Corticium sp. (366) and Ircinia felix (352), using 16S rRNA-based approaches, such as gene libraries, FISH, and DGGE. Broad congruence between larva-and adult-associated microbial communities in these studies indicated that a significant subset of the resident microbes is transferred in this way.…”
Section: Ecological Aspects: From Single Cells To the Global Scale Esmentioning
confidence: 99%